Expression, prognostic value and potential immunotherapeutic target of COL1A1 in colon cancer: COL1A1 in colon cancer - Zeng, Xiang; Chen, Guoxue; Guo, Dunwei; Chen, Yong; Hu, Xinpeng (Cellular and Molecular Biology, 2023)
This study aimed to investigate the link between COL1A1 production and colorectal carcinoma and assess the value of prognosis and immunotherapy. For this purpose, the transcriptional level of COL1A1 was analyzed. The clinicopathological information and gene expression profile were analyzed to reveal the link between COL1A1 and clinicopathological characteristics. For bioinformatics examination, GSEA and GSVA were utilized. Correlation analysis was implemented to study the causal relationship between COL1A1 and immune checkpoint molecules and inflammation immune cell infiltration. Results showed that in colorectal cancer, COL1A1 was highly expressed and linked with a few clinicopathological characteristics, inflammation and immunological response, tumor immune cell infiltration, and immune checkpoint markers. COL1A1 might likely indicate a bad prognosis and serve as a target of immunotherapy for colon cancer.